The Effect of Entrepreneurial Education, Mindset, and Creativity on Entrepreneurial Intention of University Students: Assisted in the Mediation Role of Entrepreneurial Self Efficacy - Joddy Andrian Setiawan; Wanda Gema Prasadio Akbar Hidayat; Purnamaningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
The growth in the number of young students in Indonesia is increasing rapidly every day, making many innovative ideas emerge that are being implemented by many young people to become an attractive business. This phenomenon can be seen from various perspectives and factors that make students have high entrepreneurial intentions, namely in terms of education, mindset, creativity, and student self-confidence, which are combined to create interesting and innovative business ideas. Therefore, researchers want to conduct research on some of these factors to determine the influence of existing variables. Researchers used quantitative methods by distributing questionnaires to 133 respondents who had received education about entrepreneurship or business. Processing the data in this study using the media assisted by the SmartPLS 3 software. The results of this study show that the four factors mentioned above have a linkage and influence on the entrepreneurial intentions of respondents